2014
DOI: 10.1158/1078-0432.ccr-13-2952
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Sirt7 Exhibits Oncogenic Property and Serves as a Prognostic Factor in Colorectal Cancer

Abstract: Purpose: Sirtuins play an important role in cancer development. Sirt7, as a member of this family, is frequently overexpressed in certain carcinomas, but the oncogenic mechanism is seldom reported. In this study, Sirt7 was characterized for its role in colorectal cancer aggressiveness and underlying molecular mechanisms.Experimental Design: Quantitative PCR, Western blotting, and immunohistochemistry were performed to study Sirt7 expression in a cohort of colorectal cancer tissues and non-tumor tissues and cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 34 publications
4
99
2
1
Order By: Relevance
“…A recent study found similar results in colorectal cancer samples (CRCs) [73] . An increased expression of SIRT7 was found in colorectal cancer tissues as well as CRC cell lines (HCT116.DLD1, THC8307, HT29 and SW620).…”
Section: Role Of Sirt7 In Cancersupporting
confidence: 53%
See 2 more Smart Citations
“…A recent study found similar results in colorectal cancer samples (CRCs) [73] . An increased expression of SIRT7 was found in colorectal cancer tissues as well as CRC cell lines (HCT116.DLD1, THC8307, HT29 and SW620).…”
Section: Role Of Sirt7 In Cancersupporting
confidence: 53%
“…SIRT7 overexpressing cells also showed increased motility which was attributed to induction of mesenchymal characters in these cell lines. SIRT7 overexpression decreased E-cadherin and β-catenin expression to cause this transition and increase cell motility [73] (Fig.-4C). A study in head and neck squamous cell carcinomas, reported a decrease in expression levels of all sirtuins including SIRT7 at transcript levels [76].…”
Section: Role Of Sirt7 In Cancermentioning
confidence: 89%
See 1 more Smart Citation
“…In recent years, emerging studies have been performed on SIRT7 and provided some potential mechanisms for SIRT7 in promoting cancer development. Researches in hepatocelluar carcinoma and bladder cancer indicated that SIRT7 promoted cancer cell proliferation and was regulated by microRNA, such as miR-125a-5p and miR-125b; a research in colorectal cancer identified that SIRT7 functioned as an oncogene by activation of RAF-MEK-ERK signaling pathway and increased cancer cells motility by epithelial-tomesenchymal transition (EMT) (Han et al, 2013;Kim et al, 2013;Yu et al, 2014). However, the level of SIRT7 in ovarian malignancies and the corresponding consequences of its aberrant regulation have not been discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Another study proposed that SIRT7 can promote cell survival by suppressing ER stress in a myc-dependent mannner (Shin et al, 2013). In addition, evidence has suggested that SIRT7 was related to maintenance of cellular transformation in malignancies, such as breast, liver, bladder and colorectal cancer; it has an elevated level in cancerous tissues compared with the noncancerous and its levels are associated with tumor progression (Ashraf et al, 2006;Han et al, 2013;Kim et al, 2013;Yu et al, 2014). On the contrary, a comprehensive research on the expression level of SIRT7 in head and neck squamous cell carcinoma showed a significant down-regulation (Lai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%